Strategies for Preventing Prohibited Transactions in Islamic Digital Finance: A Reflection on Riba, Gharar, and Maysir - Asia, Nurul; Semaun, Syahriyah (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2025)
The rapid expansion of digital financing products presents both opportunities and challenges to maintaining compliance with Islamic financial principles, especially concerning prohibitions against riba and gharar. This study analyzes Islamic financial management strategies to prevent non-compliant transactions within the digital financing ecosystem. Using a qualitative literature approach combined with thematic analysis of academic works, fatwas, and regulatory documents, the study identifies five dominant factors influencing sharia compliance: contractual clarity, information transparency, internal supervision, technological integration, and user literacy regarding digital contracts and transaction risks. The thematic analysis further revealed that institutions applying integrated monitoring and user education frameworks demonstrate higher compliance levels than those relying solely on contractual formalities. The findings suggest the necessity of a measurable Islamic financial management model that aligns contract design, risk control, and technology-based supervision to ensure that digital financing products are not only sharia-compliant but also effective in achieving the objectives of maqāṣid al-syarī‘ah.